Cuphophyllus striatus (Cuphophyllaceae, Agaricales), a new species from southwestern China - Xia, Wenxiao; Wang, Chaoqun; Li, Taihui; Deng, Wangqiu; Yue, Haimei; Zhang, Ming (Phytotaxa, 2025)
Cuphophyllus striatus is described as a new species from Guizhou Province of China based on morphological and molecular evidence. Morphologically, it is characterized by its small-sized basidiomata, the brownish orange to light brown pileus surface with light orange radial striae, and subglobose basidiospores 6.5–9(9.5) × 6–8(9.5) μm. In the ITS phylogenetic tree, C. striatus forms an independent clade within the genus Cuphophyllus, and close to C. cinerellus, C. esteriae and C. lamarum, but they are clearly distinct in macro- and micro-morphology. Detailed description, illustrations, comparison with related species and the phylogenetic placement are provided.